Quantitative study of the myenteric plexus of the stomach of rats with streptozotocin-induced diabetes - Fregonesi, Cristina Elena Prado Teles [UNESP]; Miranda-Neto, Marcílio Hubner de; Molinari, Sônia Lucy; Zanoni, Jacqueline Nelisis (Academia Brasileira de Neurologia (ABNEURO), 2001)
A proposta deste trabalho foi estudar as alterações morfológicas e quantitativas dos neurônios do plexo mientérico do estômago de ratos com diabetes induzido por estreptozootocina e estabelecer uma comparação com animais não diabéticos. Amostras do corpo do estômago foram submetidas a preparados de membrana corados pelo método da NADH-diaforase e a cortes histológicos corados por hematoxilina-eosina. Observou-se que o diabetes provoca significante redução no número de neurônios.

The purpose of the present study was to investigate the morphological and quantitative alterations of the myenteric plexus neurons of the stomach of rats with streptozotocin-induced chronic diabetes and compare them to those of non-diabetic animals. Samples from the body of the stomach were used for whole-mount preparations stained with NADH-diaphorase and for histological sections stained with hematoxylin-eosin. It was observed that diabetes cause a significant decrease on the number of neurons.
Estudo quantitativo do plexo mientérico do estômago de ratos com diabetes induzido por estreptozootocina
Keywords: plexo mientérico; diabetes; rato; myenteric plexus; diabetes; rat